FACTORS THAT INFLUENCING CREATIVE ACCOUNTING PRACTICES AT MANUFACTURING COMPANY THAT LISTED ON INDONESIA STOCK EXCHANGE - Maureen Maudia; Puji Lestari; Laeli Budiarti (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, 2022)
Abstract There is a loophole in regulation and policies. The act of optimizing the loophole in accounting regulation and policies is called as creative accounting. Therefore, this research aims to investigate whether the bonus compensation, leverage, and profitability are factors that influencing creative accounting. The population taken as objects of observation are 162 manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2017-2019. Sample selection is done by using the purposive sampling method. This research obtained a sample of 32 manufacturing companies listed on Indonesia Stock Exchange. This research uses three periods, so there are 96 sample data. This research is used panel data regression with EViews program. The results showed that the higher bonus compensation is followed by higher creative accounting. The higher leverage is followed by higher creative accounting. The higher profitability is followed by the higher creative accounting.